Effects of early blood pressure reduction on cognitive function in patients with acute ischemic stroke. Issue 9 (December 2016) - Bu, Xiaoqing; Zhang, Yonghong; Bazzano, Lydia A; Xu, Tan; Guo, Libing; Wang, Xuemei; Zhang, Jintao; Cui, Yong; Li, Dong; Zhang, Fengshan; Ju, Zhong; Xu, Tian; et al.
Background: The effect of early blood pressure reduction on cognitive function in patients with acute ischemic stroke remains unknown. Aim: We tested whether antihypertensive treatment would reduce cognitive impairment in patients with acute ischemic stroke. Methods: In the China Antihypertensive Trial in Acute Ischemic Stroke, patients with elevated blood pressure were randomly assigned to receive antihypertensive treatment or to discontinue all hypertensive medications within 48 h of onset. Cognitive function was measured by the Mini-Mental State Examination and Montreal Cognitive Assessment at 3 months after randomization in a subsample of 638 participants. Results: Mean systolic blood pressure was reduced by 21.5 mmHg in the antihypertensive treatment group and 13.9 mmHg in the control group within 24 h after randomization ( P  < 0.001). Mean systolic blood pressure was 134.9 mmHg in the antihypertensive treatment group and 141.6 mmHg in the control group at day 14 after randomization ( P  < 0.001). Median Mini-Mental State Examination score was 26 and Montreal Cognitive Assessment score was 22 in both the antihypertensive treatment and control groups at 3 months. An Mini-Mental State Examination < 24 was present in 30.9% of patients in the antihypertensive treatment group compared with 29.7% in the control group (odds ratio = 1.06; 95% confidence interval 0.75–1.48; P  = 0.75). Likewise, proportions of patients with Montreal Cognitive Assessment < 26 were similar between the antihypertensive treatment (70.6%) and control (70.7%) groups (odds ratio = 0.99; 95% confidence interval 0.70–1.40; P  = 0.96). Conclusions: These data indicated that early blood pressure reduction with antihypertensive medication in patients with acute ischemic stroke had no effect on cognitive impairment at 3 months.